The role of intellectual capital in improving the quality of services - field research in Marjan Medical City in Babil Governorate - Mahmoud Fahd al-Dulaimi,; Emad Abdul Amir Al Hassani, (Iraqi Journal for Administrative Sciences, 2025)
Health services are considered one of the highest priorities for all countries because they have a major role in the progress and development of countries because they are concerned with human health, and no development or progress can be achieved without them. In the past, it was said that a healthy mind means a healthy body, and based on this saying, in order to provide a scientific contribution to evaluating the quality of health services provided. In Iraqi hospitals in general, and Marjan Medical City Hospital in particular, as a model of the reality of these services, as the Iraqi health sector, like other sectors, has suffered from the bad conditions that have surrounded the country since the year (1980) until the present time due to the conditions of war, economic blockade, occupation, and political instability, and in order to improve the reality of These services: This research sought to determine the impact of intellectual capital in improving the quality of health services provided at Marjan Medical City in the city of Hilla, the center of Babil Governorate, and to circulate it to the rest of the health institutions in the country. One of the most important questions that the research attempts to answer is whether intellectual capital Helps improve the quality of health services in Marjan Medical City?). More specifically, it attempts to answer many questions that together constitute the problem of the study. The most prominent of these questions is: What are the steps that must be followed by the hospital under study to provide high-quality health services through the presence of intellectual capital? The research sought to achieve a set of goals, the most important of which are: 1- Determine the extent of the researched hospital’s ability to compete in order to provide distinguished health services through the presence of a distinct role for intellectual capital. 2 - Study the actual reality of the investigated hospital and reveal its capabilities in adopting or applying quality management in providing health services through intellectual capital and developing solutions and treatments through the results reached by the current research.